2010
DOI: 10.1016/j.ijpara.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Bm86 homologues and novel ATAQ proteins with multiple epidermal growth factor (EGF)-like domains from hard and soft ticks

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 33 publications
(34 reference statements)
7
36
0
2
Order By: Relevance
“…* Either RA257 or RAE/CTVM1 was used in experiments with R. appendiculatus cells** REE/CTVM28 was derived by a standard technique from embryos of a South African strain of R. evertsi (Nijhof et al 2010) and was grown at 28 °C in L15/MEM medium (Bell-Sakyi 2004). The parent R. evertsi ticks were kindly provided by Dr. Ard Nijhof and Prof. Frans Jongejan, Utrecht Centre for Tick-borne Diseases, Utrecht University, The Netherlands…”
Section: Methodsmentioning
confidence: 99%
“…* Either RA257 or RAE/CTVM1 was used in experiments with R. appendiculatus cells** REE/CTVM28 was derived by a standard technique from embryos of a South African strain of R. evertsi (Nijhof et al 2010) and was grown at 28 °C in L15/MEM medium (Bell-Sakyi 2004). The parent R. evertsi ticks were kindly provided by Dr. Ard Nijhof and Prof. Frans Jongejan, Utrecht Centre for Tick-borne Diseases, Utrecht University, The Netherlands…”
Section: Methodsmentioning
confidence: 99%
“…Nijhof et al (2010) have recently identified a novel protein from metastriate ticks with structural similarities to BM86, named ATAQ after a part of its signature peptide. Although its function is unknown, ATAQ is expressed in both midguts and Malpighian tubules, while BM86 is expressed only in midguts.…”
Section: Specific Tick Antigens and Their Effect On Pathogen Transmismentioning
confidence: 99%
“…The Bm86 glycoprotein is located on the luminal surface of the plasma membrane of tick gut epithelial cells it is able to stimulate a protective immune response in cattle against subsequent tick infestation [23]. The phylogeny of this gene has been mainly studied in Rhipicephalus genus and obtained concordant results with data of the ticks' systematic [24].…”
Section: Introductionmentioning
confidence: 82%